The 12th Conference of the International Sports Engineering Association 2018
DOI: 10.3390/proceedings2060234
|View full text |Cite
|
Sign up to set email alerts
|

Giving Inertial Sensor Data Context for Communication in Applied Settings: An Example of Visual Exploration in Football

Abstract: Abstract:For an athlete to make an appropriate decision and successfully perform a skill, they need to perceive opportunities for action by visually exploring their environment. The head movements that support visual exploration can easily and accurately be recorded using Micro-ElectroMechanical Systems (MEMS) Inertial Measurement Units (IMU) in research and applied settings. However, for IMU technology to be effective in applied settings, practitioners need to be able to communicate data to coaches and player… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The influence of the novelty effect should be further investigated. Previous research showed the importance of understanding the total radial distance covered by a player's head during a head turn [57] [58]. Additionally, the various benefits of visually scanning the surroundings before receiving the ball have been reported [9][23] [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of the novelty effect should be further investigated. Previous research showed the importance of understanding the total radial distance covered by a player's head during a head turn [57] [58]. Additionally, the various benefits of visually scanning the surroundings before receiving the ball have been reported [9][23] [5].…”
Section: Discussionmentioning
confidence: 99%
“…These displayed possible passing options. However, this setup gives the test subject a predefined idea of where to look for relevant information, conditioning his movement to predefined vectors [58]. By contrast, for the VR simulation in this paper, the whole FoR area was an option for the player.…”
Section: Discussionmentioning
confidence: 99%
“…Housed in an elastic headband and worn at the back of the player’s head, these devices allow time-efficient data collection and analysis on whole teams of players and provide sensitive and objective data collection that is able to detect the rapid head movements used by footballers in live match-play. Together, the variables obtained from head-mounted IMUs reported in this study give an indication of how often a player explores their environment (i.e., the rate of exploration – frequency) and how much of the environment a player explores (excursion) before gaining possession of the ball (McGuckian et al, 2018a).…”
Section: Introductionmentioning
confidence: 97%
“…Another important aspect of visual exploration in football, related to how much of the environment a player has explored, is the total radial distance of a head turn, here termed excursion . Despite giving an understanding of the magnitude of a head turn, and being recognized to be an important aspect of exploration (Jordet and Pepping, 2018; McGuckian et al, 2018a,b), previous quantification of exploration through manually counting head movements is unable to accurately quantify excursion. For this reason, exploration excursion has thus far not received any attention in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation